From Corporatism to Public Utilities: Workplace Pensions in the 21st Century. - Clark, G (School of Geography and Environment (University of Oxford), 2011)
For many OECD countries, workplace pensions have been an important mechanism for supplementing state-sponsored social security. Notwithstanding significant differences between developed economies in the significance attached to workplace pensions, provision has been typically encouraged through preferential tax policies and corporate benefits and compensation packages. If relevant for the looming retirement of the baby-boom generation, it is doubtful that these arrangements will be as important for future generations. As state-sponsored social security has been discounted in terms of promised value and entitlement, traditional workplace pensions have been closing and replaced by retirement saving instruments that are neither as lucrative nor as dependable in terms of final value. Recognising the retrenchment in workplace pensions, governments have sought to encourage and, in some cases, develop different types of retirement savings institutions. This paper charts the decline of traditional workplace pensions, the apparent inadequacy of alternatives such as money purchase (defined contribution) schemes, and the rise of what are referred to as 'public utilities': government sponsored savings institutions that are designed to compensate for the decline (in coverage and promised value) of workplace pensions albeit at a more modest level than that associated with traditional defined benefit schemes. In doing so, I draw upon the experience of the US and the UK, Australia, Canada, and New Zealand, as well as developments in Germany and continental Europe. Essentially, it is argued that the rise of public utilities in this domain is indicative of the transformation of corporate capitalism over the past 25 years and the inability of governments to shoulder the retirement costs of their ageing societies in an era of global financial integration.